2021
DOI: 10.25259/sni_664_2021
|View full text |Cite
|
Sign up to set email alerts
|

The effect of radiation therapy and chemotherapy on malignant craniopharyngioma: A review

Abstract: Background: Malignant craniopharyngioma is a rare tumor with few published case reports. It can form de novo or transform from a benign variant and is associated with a dismal survival rate. We reviewed the literature for all published cases and studied the effect of radiation on the rate of malignant transformation. We analyzed the effect of chemotherapy on survival. Methods: We used various search engines to locate literature from 1980 onward and identified 31 case reports, one of which was excluded. Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Craniopharyngiomas are associated with substantial morbidity. Although, CPs can be highly aggressive and have a tendency to recur following surgical removal, the literature indicates that it seldom establishes malignant behavior [5]. Aggressive behavior of the tumor is reflected by its tendency towards damaging of adherent structures [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Craniopharyngiomas are associated with substantial morbidity. Although, CPs can be highly aggressive and have a tendency to recur following surgical removal, the literature indicates that it seldom establishes malignant behavior [5]. Aggressive behavior of the tumor is reflected by its tendency towards damaging of adherent structures [7].…”
Section: Discussionmentioning
confidence: 99%
“…The epithelium in AdaCP develops in cords, lobules, and whorls, with palisading peripheral columnar epithelium and loosely organized stellate reticulum. This type is distinguished by "wet" keratin [5]. PaCPs feature well-differentiated monomorphic squamous epithelium covering fibrovascular cores with thin capillary blood vessels and dispersed immune cells including macrophages and neutrophils, and have a smoother surface than AdaCPs, which aids excision.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant CP was first described in 1973 as a de novo squamous carcinoma arising from an intrasellar epidermal cyst [ 75 ]. Malignant transformation of CP is extremely rare and generally arises from an adamantinomatous subtype (73 %) [ 76 , 77 ]. Malignant CP appears to present the following features: (i) marked nuclear atypia; (ii) a high nucleus-to-cytoplasm ratio; (iii); robust mitotic activity; and (iv) other histologic features such as solid growth pattern, destruction of the basement membrane, infiltrative growth, microvascular proliferation and so on [ 77 , 78 ].…”
Section: Malignant Transformation Of Craniopharyngiomamentioning
confidence: 99%
“…Malignant transformation of CP is extremely rare and generally arises from an adamantinomatous subtype (73 %) [ 76 , 77 ]. Malignant CP appears to present the following features: (i) marked nuclear atypia; (ii) a high nucleus-to-cytoplasm ratio; (iii); robust mitotic activity; and (iv) other histologic features such as solid growth pattern, destruction of the basement membrane, infiltrative growth, microvascular proliferation and so on [ 77 , 78 ]. The etiology and pathogenesis of malignant CP are unclear, though some authors presumed a probable correlation with radiotherapy [ 78 ].…”
Section: Malignant Transformation Of Craniopharyngiomamentioning
confidence: 99%
“…Despite its current WHO grade I classification with no malignant subtype, more and more case reports of a malignant form of CP occurring de novo or transforming from a benign variant have been published in recent years [4][5][6][7][8][9][10]. The exact pathogenesis and biological behavior of malignant change in CP are not yet clear; however, some reports have suggested that radiation may be a contributing factor to carcinogenesis [4,6,7,9] though such a link has not been proven yet by any studies with high level of evidence [8,11,12]. Although malignant CP is still a rare clinical entity with less than 40 reported cases in the current literature, it may induce a new update in the WHO classification system in the future.…”
Section: Terminology and Stagingmentioning
confidence: 99%